Pengembangan SDM Syariah Melalui Perguruan Tinggi: Studi Kasus di Program Studi Manajemen Perbankan Syariah FAI UMJ - Syaifullah, Hamli (BISNIS, 2019)
This study wants to find out how big is the role of Higher Education that provides Islamic Banking Management to produce qualified, qualified human resources, and according to the wishes of the Islamic Banking industry. This research takes a case study in the Islamic Banking Management, Faculty of Islamic Studies-Jakarta Muhammadiyah University, in order to get more focused research. In analyzing data, researchers used a qualitative descriptive method. From this study, the researcher proposes that all Higher Education that have the Islamic Banking Management direct the curriculum required by the Islamic Banking industry.